Molecular Docking of Nigella Sativa L. with PXR Receptors and the Effect of Thymoquinone on PXR Expression in HepG2 Cells - Megawati, Annik; Nurrochmad, Arief; Nugroho, Agung Endro; Lukitaningsih, Endang; Marbun, Prajona (Molekul, 2024)
ABSTRACT. The interaction between herbal remedies and drugs is a fascinating phenomenon that might cause therapeutic complications in patients. Warfarin is an anticoagulant drug that provides anti-blood-clotting effects by inhibiting the formation of vitamin K-dependent coagulation factors, and warfarin interacts with the nuclear receptor PXR, subsequently modulating cytochrome P450 during the metabolism process. St. John's wort, an herbal medicine with antidepressant effects, can alter the pharmacokinetics of warfarin. Thymoquinone is one of the active compounds in N. sativa and has pharmacological activities such as anticoagulant, antidiabetic, diuretic, antidepressant, and anti-inflammatory effects. In this study, we investigated the compounds in Nigella sativa (N. sativa) against pregnane X receptor (PXR) and evaluated the impact of thymoquinone (TQ) administration on PXR expression in HepG2 cells. The molecular docking analysis was conducted utilizing the Molecular Operating Environment (MOE) with the PXR (PDB ID: 7AXJ). At the same time, the PXR gene expression was measured using RT-PCR instruments. The RMSD value in docking represents the deviation criteria between the native ligand position and the redocking position result, indicating the capability of MOE and PDB qualification for performing molecular docking. The docking analysis showed that warfarin had the strongest binding energy (7AXJ -6.0507) by forming hydrogen binding type on Arg410. Despite TQ being the major component, it also displayed a high affinity for the two PDB IDs (7AXJ -4.5962). Furthermore, the concurrent administration of warfarin and TQ (19.27 μM) in HepG2 cells showed a significant reduction in the relative mRNA expression of the PXR gene. Given the above-mentioned findings, our study adequately enables us to predict the mechanism behind herb-drug interactions (HDIs) implicating N. sativa, specifically the TQ compound to warfarin metabolism via the activation of the PXR receptor. Keywords: Thymoquinone, expression mRNA, PXR, molecular docking, HepG2 cells.